2015
DOI: 10.1093/jisesa/iev082
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Putative Carboxylesterase and GlutathioneS-transferase Genes from the Antennae of theChilo suppressalis(Lepidoptera: Pyralidae)

Abstract: In insects, rapid degradation of odorants in antennae is extremely important for the sensitivity of olfactory receptor neurons. Odorant degradation in insect antennae is mediated by multiple enzymes, especially the carboxylesterases (CXEs) and glutathione S-transferases (GSTs). The Asiatic rice borer, Chilo suppressalis, is an economically important lepidopteran pest which causes great economic damage to cultivated rice crops in many Asian countries. In this study, we identified 19 putative CXE and 16 GST gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 61 publications
4
32
1
Order By: Relevance
“…To test whether this characteristic was shared with the other members of the subclade, we first searched for SP in the sequence of AtraGST (Leal et al, 2009), MsexGST-msolf (Robertson et al, 1999; Rogers et al, 1999), CsupGSTd1 (Liu et al, 2015a) and CmedGSTd1 (Liu et al, 2015b) and we indeed identified putative SPs for all them. We then completed by bioinformatics the N-terminus sequences for the 5 other genes from this clade ( SfruGSTd2, HarmGSTd02, BmGSTd1, EposGST11 , and PxylGSTd1 ) and we also identified predicted SP for each of them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether this characteristic was shared with the other members of the subclade, we first searched for SP in the sequence of AtraGST (Leal et al, 2009), MsexGST-msolf (Robertson et al, 1999; Rogers et al, 1999), CsupGSTd1 (Liu et al, 2015a) and CmedGSTd1 (Liu et al, 2015b) and we indeed identified putative SPs for all them. We then completed by bioinformatics the N-terminus sequences for the 5 other genes from this clade ( SfruGSTd2, HarmGSTd02, BmGSTd1, EposGST11 , and PxylGSTd1 ) and we also identified predicted SP for each of them.…”
Section: Resultsmentioning
confidence: 99%
“…However, the expression of GSTs as well as their activities have been also highlighted in the olfactory organs of several insect species. Antennal expressed GSTs have been indeed identified in various moth species, such as Manduca sexta (Rogers et al, 1999), Helicoverpa armigera (Wang et al, 2004), Amyelois transitella (Leal et al, 2009), Bombyx mori (Tan et al, 2014), Chilo suppressalis (Liu et al, 2015a), Epiphyas postvittana (Corcoran et al, 2015), Cnaphalocris medinalis (Liu et al, 2015b), and Cydia pomonella (Huang et al, 2017), but also in the fruit fly Drosophila melanogaster (Younus et al, 2014) or in the beetles Agrilus planipennis (Mamidala et al, 2013), Dendroctonus valens (Gu et al, 2015), and Phyllotreta striolata (Wu et al, 2016). This particular localization led to the hypothesis of a possible dual function of GSTs in antennae where, besides their original implication in xenobiotic metabolism, they could play a role in the signal termination and in odorant clearance, as Odorant-Degrading Enzymes (ODEs, Vogt and Riddiford, 1981; Chertemps, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…So far, a variety of antennal‐specific and abundant ODE genes of insects have been identified via transcriptome and sequencing. The ODE family genes usually consist of esterase (He et al, ; Vogt & Riddiford, ), aldehyde oxidase (Merlin et al, ; Pelletier et al, ; Y. X. Zhang, Wang, Li, Li, & Liu, ), alcohol dehydrogenase (ADHs; Huang, Liu, Su, & Feng, ), glutathione S ‐transferase (GST; S. Liu, Gong, Rao, Li, & Li, ; X. Tan et al, ), cytochrome P450 oxidoreductase (Hovemann, Sehlmeyer, & Malz, ), and carboxylesterase (CXEs; Chertemps et al, ). GST belong to a kind of important ODEs and play a vital role in phase II enzymic detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…Chilo suppressalis individuals used in this study originated from a field population collected at an experimental farmland at Anhui Agricultural University, Hefei, Anhui, China (Liu, Gong, Rao, Li, & Li, ). Larvae were reared in our laboratory with rice seedlings, and adult moths were fed on a 10% (v/v) honey solution.…”
Section: Methodsmentioning
confidence: 99%